Slab waveguide theory for general multi-slot waveguide. Issue 13 (19th July 2016) - Le, ZiChun; Yin, LiXiang; Zou, Yu; Wu, Xiang
Abstract: Optical devices based on slot waveguide are of considerable interest in numerous applications due to the distinct feature of strong electric field confinement in a low-refractive index region. A theoretical model based on multi-slab waveguide theory is used to reveal the physical mechanism of the slot waveguide. The calculation results derived from the basic Helmholtz equation for the conventional single-slot waveguide with a 2% validation of the effective refractive index are compared to the former experiment results by the Cornell University group. Moreover, we extend the theoretical model to a general multi-slot waveguide. Its electric field distribution and key properties such as optical power confinement factor and enhancement factor in slot are deduced theoretically and fully discussed.